Coexistence of calcified- and lipid-containing plaque components and their association with incidental rupture points in acute coronary syndrome-causing culprit lesions: results from the prospective OPTICO-ACS study. (14th December 2021) - Abdelwahed, Youssef S; Nelles, Gregor; Frick, Clara; Seppelt, Claudio; Meteva, Denitsa; Stähli, Barbara E; Rai, Himanshu; Riedel, Matthias; Skurk, Carsten; Rauch-Kröhnert, Ursula; Haghikia, Arash; Sinning, David; et al.
Abstract: Aims: Rupture of the fibrous cap (RFC) represents the main pathophysiological mechanism causing acute coronary syndromes (ACS). Destabilization due to plaque biomechanics is considered to be importantly involved, exact mechanisms triggering plaque ruptures are, however, unknown. This study aims at characterizing the relation between plaque components and rupture points at ACS-causing culprit lesions in a large cohort of ACS-patients assessed by high-resolution intracoronary imaging. Methods and results: Within the prospective, multicentric OPTICO-ACS study program, the ACS-causing culprit plaques of 282 consecutive patients were investigated following a standardized optical coherence tomography (OCT) imaging protocol. Each pullback was assessed on a frame-by-frame basis for the presence of lipid components (LC), calcium components (CC), and coexistence of both LC and CC (LCC) by two independent OCT-core labs. Of the 282 ACS-patients, 204 patients (72.3%) presented with ACS caused by culprit lesions with rupture of the fibrous cap (RFC-ACS) and 27.7% patients had ACS caused by culprit lesions with intact fibrous cap (IFC-ACS). When comparing RFC-ACS to IFC-ACS, a preferential occurrence of all three plaque components (LC, CC, and LCC) in RFC-ACS became apparent ( P < 0.001). Within ruptured culprit lesions, the zone straight at the rupture point [extended rupture zone (RZ)] was characterized by similar (24.7% vs. 24.0%; P = ns) calcium content when compared with the proximal and distal border of the culprit lesion [border zone (BZ)]. The RZ displayed a significantly higher amount of both, LC (100% vs. 69.8%; P < 0.001) and LCC (22.7% vs. 6.8%; P < 0.001), when compared with the BZ. The relative component increase towards the RZ was particularly evident for LCC (+233.8%), while LC showed only a modest increase (+43.3%). Conclusions: Calcified- and lipid-containing components characterize ruptured fibrous cap ACS-causing culprit lesions. Their coexistence is accelerated directly at the ruptured point, suggesting a pathophysiological contribution in the development of RFC-ACS. Graphical Abstract: